Development of a full-length infectious clone of sunflower chlorotic mottle virus (SuCMoV) - Bejerman, Nicolas Esteban (2013)
A full-length cDNA clone (p35SuCMoV) of the sunflower chlorotic mottle virus common strain (SuCMoV-C) genomic RNA was constructed. Three cDNA fragments covering the whole genome of SuCMoV-C were cloned between a cauliflower mosaic virus 35S promoter and a nopaline synthase terminator. Mechanical inoculation of sunflower and Nicotiana occidentalis seedlings with p35SuCMoV DNA led to systemic infection. Symptoms induced by p35SuCMoV were similar to those caused by the wild-type SuCMoV-C but appeared four days later. Infection was confirmed by a western blot test, electron microscopy, RT-PCR and inoculation of progeny virions to sunflower seedlings. This is the first report about the construction of a biologically active, full-length cDNA copy of the SuCMoV-C RNA genome.